Segundo seminario/taller de la Red regional de información sobre banano y plátano de America Latina y el Caribe, 10-11 de Julio 1997, San José, Costa Rica - Picq, C.; International Network for the Improvement of Banana and Plantain (1998)
To develop the draft work plans, agreements and funding strategies, this Regional Coconut Genebank Workshop was conducted in Riau, Pekanbaru, Indonesia near the site of one of the ICGs, from 26 to 28 February 1996.